Urban Green and Environmental Processes: Towards a Multifunctional Landscape Design - Pelorosso, Raffaele; Gobattoni, Federica; Lopez, Nicola; Leone, Antonio (TeMA - Journal of Land Use, Mobility and Environment, 2013)
Urbanisation phenomena, associated with soil sealing, can lead to an increase in surface runoff, environmental pollution and ecosystems degradation with risks to human health and economic losses by floods. Then, new urban development strategies and land management models are essential. The European Union Water Framework Directive (2000) requires Member States to draw up efficient measures to ensure sustainable use of water resources. Several Best Management Practices (BMPs) were developed at this aim. BMPs are usually multifunctional structures (e.g. wetland and green roofs) that can provide suitable Habitat for species and bring to the maintenance of biodiversity, allow climate regulation by evaporation and adsorption of solar radiation together with aesthetic/amenity, recreational and educational benefits, enhancing the urban quality of life and social interaction. However, especially in Italy, the full integration of BMPs in territorial planning and urban (re-) design is not fully realized yet. The control of water quality and quantity has often been realized by isolated and localized interventions (e.g. detention/infiltration basins) without a “smart” and systemic project based on a holistic environmental sustainability concept. Through an application of a synthetic index for urban permeability assessment (RIE Index), this paper presents a systemic approach to urban green planning to reduce surface runoff in a pilot area of Bari city, increasing soil permeability and reducing hydraulic risk. This green and sustainable stormwater management approach would be able to furnish environmental benefits and services to the citizens, enhancing quality of life in urban contexts.